Implementation of Inquiry Based Learning Model to Improve Cognitive Learning Outcomes in SKI Subjects at MI Sunan Gunung Djati - Wendi Saepul Mikdar; Ridho Budi Utomo; Muhammad Ali; Qiqi Yuliati Zaqiah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The purpose of this study was to determine the effect of the application of the inqury-based learning model on SKI subjects at MI Sunan Gunung Djati. Based on the results of initial observations, students' cognitive learning outcomes declined, this was indicated by the large number of children whose daily scores were below the KKM. These problems need to be overcome by using the right way, in this study the solution used is the IBL learning model. This research uses descriptive qualitative methods. The Inquiry Based Learning model is an educational approach that emphasises the role of students in the learning process, encouraging them to be actively involved with the subject matter through questioning, exploration, and problem solving. the results show that students’ cognitive learning that can be observed, namely students’ daily grades, has increased, students are able to understand the material taught and are able to tell or explain back the material that has been delivered.